Improving Safety Awareness in the Workforce through Education and Programs: A Scoping Review - Nurdiansyah, Warid; Lestari, Fatma (Testing Center for Oil and Gas LEMIGAS, 2026)
Approximately two million people die annually from occupational diseases and workplace accidents. Despite extensive preventive measures, accident and fatality rates remain high, with recurring incidents and persistent root causes. These patterns highlight the urgent need for effective programs and educational models to enhance workers’ safety awareness, a critical factor in preventing occupational accidents. This study conducted a scoping review to map existing evidence, conceptual frameworks, and research gaps concerning safety awareness programs and educational interventions for workers. Following the PRISMA-ScR framework, three databases: Medline (PubMed), APA PsycArticles® (ProQuest), and Scopus, were systematically searched for English-language studies published in the past five years. Ten studies met the inclusion criteria. Although research in this area remains limited, evidence suggests that well-designed programs and educational approaches, particularly those integrating technology-based learning and participatory methods, can effectively improve workers’ safety awareness. Further empirical studies are needed to develop comprehensive, evidence-based educational models applicable across diverse occupational settings.